1987
DOI: 10.1530/acta.0.1150289
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal profile in pubertal females with chronic renal failure: Before and under haemodialysis and after renal transplantation

Abstract: The effects of chronic renal failure on the hypothalamic-pituitary-ovarian axis in 25 girls, aged 9.1 to 20.9 years (mean 13.8) were studied. Twelve patients on conservative treatment (group A) had serum creatinine values between 176.8 and 1502.8 \g=m\mol/l; 9 patients were on haemodialysis (group B); and 12 patients had received a renal transplant (group C). Tanner stage of breast development was delayed relative to chronological age in 5 out of 18 patients. Serum oestradiol was normal or low when related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Finally, the plasma concentration of inhibin is elevated [21]. In females estradiol levels tend to decrease in proportion to the decrease in GFR [22]. …”
Section: Pathogenesis Of Growth Delay In Ckdmentioning
confidence: 99%
“…Finally, the plasma concentration of inhibin is elevated [21]. In females estradiol levels tend to decrease in proportion to the decrease in GFR [22]. …”
Section: Pathogenesis Of Growth Delay In Ckdmentioning
confidence: 99%
“…Earlier studies in prepubertal (Oertel et al 1983) and pubertal (Ferraris et al 1980(Ferraris et al , 1987 children with CRF have demonstrated an abnormal pitui¬ tary response to an intravenous bolus of high-dose GnRH, suggesting a hypothalamo-pituitary disor¬ der as the likely aetiology of delayed pubertal de¬ velopment. However, bolus GnRH tests are diffi¬ cult to interpret, due to elevated baseline serum LH levels and reduced metabolic clearance rates in CRF.…”
Section: Discussionmentioning
confidence: 96%
“…Children with CRF may have pubertal develop¬ ment which is delayed or disordered (Ferraris et al 1980(Ferraris et al , 1987Schärer et al 1976;Rizzoni et al 1986;van Diemen-Steenvorde et al 1987). Several endo¬ crine abnormalities such as low or subnormal gonadal steroids and elevated gonadotropin concen¬ trations in plasma have been reported in pre¬ pubertal (Oertel et al 1983) as well as in pubertal (Ferraris et al 1980(Ferraris et al ,1987 children with CRF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Esse fato poderia explicar os níveis baixos de FSH, por um efeito de bloqueio do eixo hipotálamo-hipofisário determinado pelo contraceptivo. Neste grupo, houve concordância com a maior parte da literatura no tocante às dosagens de FSH, que se mostram dentro da normalidade; nas dosagens de LH, embora muitos autores relatem níveis elevados 26,23,31,36,37 , não encontramos nenhum valor acima do considerado normal. Também aqui houve uma paciente com níveis ligeiramente diminuídos: trata-se de portadora de lúpus eritematoso sistêmico submetida a corticoterapia crônica com prednisona.…”
Section: Discussionunclassified